2022
DOI: 10.1063/5.0124552
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic loss analysis in a pump-turbine with special emphasis on local rigid vortex and shear

Abstract: Since the pump as turbine (PAT) is increasingly employed in energy storage, improving efficiency in both pump and turbine modes is required for economic benefits. This study aims to analyze the vortex flow characteristics and vortex control methods in both modes to reduce hydraulic loss. In this paper, a delayed detached eddy simulation (DDES) was applied in a low specific speed pump-turbine. Based on the entropy production analysis and vorticity binary decomposition in the local vortices, the results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Axial-flow pumps working as turbines (pump as turbine, PAT) not only generate clean energy but also generate considerable economic benefits [5]. Compared with traditional turbine units, PATs have a simple structure, low cost, and easy maintenance, making them highly suitable for facilitating the sustainable use of water resources in remote rural regions [7,8]. However, the design and manufacture of axial-flow pumps usually only consider the performance under conventional pump conditions, rather than reverse operating conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Axial-flow pumps working as turbines (pump as turbine, PAT) not only generate clean energy but also generate considerable economic benefits [5]. Compared with traditional turbine units, PATs have a simple structure, low cost, and easy maintenance, making them highly suitable for facilitating the sustainable use of water resources in remote rural regions [7,8]. However, the design and manufacture of axial-flow pumps usually only consider the performance under conventional pump conditions, rather than reverse operating conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et. Al [17][18][19] reported the influence of local rigid vortex that the local shear effect was dominant in energy loss in a centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…Ono et al investigated the relation between the leading edge radius and the S-shaped characteristics and found that the leading edge vorticity causes the inner blade loss [13]. Yuan et al analyzed vortex flow characteristics and vortex control methods in both modes to reduce hydraulic loss [14]. Fu et al used the single-and twophase flow models to demonstrate the influence of cavitation on pressure fluctuation in a pump-turbine [15].…”
Section: Introductionmentioning
confidence: 99%